Preparation and characterization of surfactant loaded clays as drug adsorbents - ÇALIŞKAN SALİHİ, ELİF; CANTÜRK TALMAN, REMZİYE YEŞİM; GÖKTÜRK, SİNEM (TAYLOR & FRANCIS INC, 2022)
Natural clays have many advantages in order to be used in the pharmaceutical industry. However surface modification is needed for the adsorption of low or moderately water-soluble drug molecules on clays such as bentonite. Four surfactant loaded clays were prepared, characterized and tested for paracetamol loading in this study. Organoclays were characterized using FTIR, Raman, XRD and SEM-EDX analysis. Characterization studies confirmed the successful intercalation of surfactant molecules into bentonite. Then organoclays were tested for drug loading using paracetamol which is a widely used analgesic drug . Loading tests showed the improved adsorption capacity of bentonite after modification with surfactants. DTAB loaded bentonite showed the highest adsorption capacity for paracetamol and surfactants followed the order as DTAB > DPC > SDS > DBSA to be more effective on the adsorption capacity of bentonite. Paracetamol adsorption on organoclays was due to hydrophobic interaction with the contribution of pi dispersion interactions.
Keywords: Bentonite; clay; surfactant; paracetamol; drug; MODIFIED ORGANO-MONTMORILLONITE; DICLOFENAC-SODIUM; DELIVERY-SYSTEMS; ADSORPTION; RELEASE; EQUILIBRIUM; PARACETAMOL; REMOVAL; CARRIER; CTAB